CORRECTION OF METABOLIC CHANGES OF TISSUES OF RATS ORAL CAVITY BY COMPLEX OF PREPARATIONS UNDER CONDITIONS OF INTRAUTERINE HYPOXIA AND CARIOGENIC DIET - Ivanov, V.S.; Dienha, O.V.; Shnaider, S.A.; Pyndus, T.O.; Pyndus, V.B.; Shchepanskyy, F.Y. (World of Medicine and Biology, 2021)
The research is dedicated to the study of the effect of the complex of preparations on the dental status and the state of the tissues of the oral cavity of rats under conditions of intrauterine hypoxia and cariogenic diet. The experiment was carried out on 35 white rats of both sexes: 29 female and 6 male rats. It was revealed caries-prophylactic effect and a decrease in the aggressiveness of the pathological process under the action of the complex in the conditions of intrauterine tissue hypoxia and cariogenic diet. The complex showed an anti-inflammatory effect in the oral mucosa. The levels of metabolic markers of pyruvate hypoxia in the liver and in the oral mucosa returned to normal state. The complex significantly improved the state of collagen and glycosaminoglycans in the parodontal bone tissue.